Hepatocellular Carcinoma In Malaysia And Its Changing Trend - Ruksana Raihan; Fatiha H Shabaruddin; Rosmawati Mohamed; Amirah Azzeri (Jaypee Brothers Medical Publishing (P) Ltd., 2024)
Indexed by WOS/ Scopus